Report on the USSR - RFE/RL, inc.; RFE/RL Research Institute. (RFE/RL, Inc., 1989)
Continues: Radio Liberty research bulletin, ISSN 0148-2548.Merger of:Report on Eastern Europe, ISSN 0937-7441; RFE/RL research report, ISSN 0941-505X.